Seasonal Impact on 3D GPR Performance for Surveying Yedoma Ice Complex Deposits - Schennen, Stephan; Wetterich, Sebastian; Schirrmeister, Lutz; Schwamborn, Georg; Tronicke, Jens (Frontiers in Earth Science, 2022)
Ground-penetrating radar (GPR) is a popular geophysical method for imaging subsurface structures with a resolution at decimeter scale, which is based on the emission, propagation, and reflection of electromagnetic waves. GPR surveys for imaging the cryosphere benefit from the typically highly resistive conditions in frozen ground, resulting in low electromagnetic attenuation and, thus, an increased penetration depth. In permafrost environments, seasonal changes might affect not only GPR performance in terms of vertical resolution, attenuation, and penetration depth, but also regarding the general complexity of data (e.g., due to multiple reflections at thaw boundaries). The experimental setup of our study comparing seasonal differences of summertime thawed and winter- and springtime frozen active layer conditions above ice-rich permafrost allows for estimating advantages and disadvantages of both scenarios. Our results demonstrate major differences in the data and the final GPR image and, thus, will help in future studies to decide about particular survey seasons based on the GPR potential for non-invasive and high-resolution investigations of permafrost properties.